2008
DOI: 10.1136/bmj.a568
|View full text |Cite
|
Sign up to set email alerts
|

Open access publishing, article downloads, and citations: randomised controlled trial

Abstract: Objective To measure the effect of free access to the scientific literature on article downloads and citations. Design Randomised controlled trial. Setting 11 journals published by the American Physiological Society. Participants 1619 research articles and reviews. Main outcome measures Article readership (measured as downloads of full text, PDFs, and abstracts) and number of unique visitors (internet protocol addresses). Citations to articles were gathered from the Institute for Scientific Information after o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
271
0
16

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(296 citation statements)
references
References 32 publications
9
271
0
16
Order By: Relevance
“…The underlying hypothesis is that a freely-available article will be read more, and thus cited more, than an article which is not freely available. Other studies report no evidence of this effect [18,19,20]. Which is the situation in HEP, where an immense Open Access advantage is already provided by arXiv?…”
Section: Is There An Advantage To Publishing In Open Access Journals?mentioning
confidence: 97%
“…The underlying hypothesis is that a freely-available article will be read more, and thus cited more, than an article which is not freely available. Other studies report no evidence of this effect [18,19,20]. Which is the situation in HEP, where an immense Open Access advantage is already provided by arXiv?…”
Section: Is There An Advantage To Publishing In Open Access Journals?mentioning
confidence: 97%
“…The Davis et al (2008) controlled study which found no citation advantage did show that OA articles had more downloads and were accessed more often than the control group. This in itself is very valuable.…”
Section: Citation Advantagementioning
confidence: 99%
“…In a well-designed controlled trial involving the random selection of articles for OA status from a publisher's corpus, no evidence was found for an OA citation advantage (Davis et al, 2008). A later study showed that only 2 out of 11 journals studied showed positive OA citation effects (Davis, 2009).…”
Section: Citation Advantagementioning
confidence: 99%
“…Several studies of article level usage found that open access articles have higher levels of usage than non-OA articles. Two different randomized controlled trials found OA articles had higher levels of downloads, and a greater number of addresses downloading them, than non-OA articles (Davis, 2011;Davis, Lewenstein, Simon, Booth, & Connolly, 2008). Two other studies found that usage of OA articles is higher not only initially after publication but continuing over time (Wang, Liu, Mao, & Fang, 2015;Wang, Mao, Xu, & Zhang, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%